PENGARUH JUMLAH PENGGILINGAN TANAH LIAT SEBAGAI BAHAN PEMBUAT GENTENG TERHADAP KARAKTERISTIK GENTENG KERAMIK DARMASABA - Ari Sanjaya, I Putu (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009, 2009)
The results of previous research on standard Pejaten ceramic tile and Pejaten ceramic tile with natural pozzolan pumice, complied with the Ceramic Tile Regulation of Indonesia NI-19, showed that none of those ceramic tiles resisted the water infiltration. The tiles constituent only received once grinding during the fabrication process. It was shown from ceramic tile industry in Darmasaba that there were physically differences between ceramic tiles with once and twice grinding. The ceramic tiles with twice grinding process had clear noise, smooth texture and fine crack at the surface. In order to improve the strength of the ceramic tiles, it was decided to conduct a research on ceramic tile characteristic with twice grinding process. The characteristic of the ceramic tiles to be determined were dry shrinkage, burnt shrinkage, bending strength, water infiltration and water absorption. The ceramic tile specimens were mixed with a ratio of 1:0.15 of clay : paras pollen batched by volume with a sufficient water amount. The research variable was a number of grinding. The result showed that the ceramic tiles with once grinding had an average water absorption of 24,80%, the average water infiltration in 3 hours was 8,6 mm and the ceramic tile was un-resistance to the water infiltration. The average bending strength of whole tile was 86 kg and the flat surface of the tile was 26 kg. The average of dry and burnt shrinkage was 7,2% and 2,2% in long direction and 6,7% and 2,1% in short direction. The bending curvature equal to 6,35 cm. The tiles with twice grinding had an average water absorption of 22,25%, the average water infiltration in 3 hours was 8,1mm and the ceramic tiles was categorized resistance to the water infiltration. The average bending strength of whole tiles was 89 kg and the flat surface of the tiles was 28 kg. The average of dry and burnt shrinkage was 6,9% and 1,9% in long direction and 6,3% and 1,8% in short direction. The bending curvature equal to 6,11 cm. The ceramic tiles were classified as the quality IV.
Keywords: Darmasaba ceramic tile, paras pollen, grinded, ceramic characteristic.